PERAN KEPUTUSAN PEMBELIAN DALAM HUBUNGAN BRAND SNEAKERS NIKE DAN LOYALITAS PELANGGAN DI KOTA SURABAYA - Simeru, Daud (Universitas Widya Kartika Surabaya, 2024)
The development and progress of the industry directly, we can see changes in the growth of the business world which has differences in the economic sector every year. This is due to the emergence of goods and services industry companies that never stop producing various kinds of goods or products that are sold to consumers. Meanwhile, in the field of sneakers, Nike products are the main products that are very popular for the quality of their products to customers, especially in the city of Surabaya. This attracted researchers to examine the role of purchasing decisions in Nike's brand relationship and customer loyalty in the city of Surabaya. Meanwhile, the method used in the research is (quantitative) with a total of 30 respondents who are specifically Nike sneakers users. The variables used in this research are, independent variables (X), dependent variables (Y) and intervening variables (Z) while to find out the results of the influence of variables by calculating through Path Analysis.